Penilaian kualitas pengembangan sistem informasi pada perusahaan distributor - Popi Diana Syafitri (UIN Sumatera Utara, 2016)
Development of information technology has fueled globalization is one among changes in the external environment that has a very significant impact on the conduct of business and society today. So much so that the necessary changes before a new paradigm to be competitive in the new business environment. To achieve that goal required organizational restructuring that leads to integrated enterprise, with information systems and integrated information technology as a means of support in business operations. Thus it is very important to know whether the information system has been quality to support all business processes of the organization.